Alienación de estereotipos culturales provenientes de la ciudad de Quito, en los programas de radio fm en Latacunga, a través de un análisis comparativo entre el programa radiación temprana de radio canela, quito, y el programa la fuga, segundo bloque, de radio Latacunga fm - Serrano Buenaño, Katherine Daniela (2016)
This research was designed as a diagnostic to lack of promotion of cultural identity in the province of Cotopaxi and its importance for young people to inform, educate, and appreciate the cultural riches and traditions that has our province . The lack of dissemination of cultural identity is one of the problems that concern greater magnitude, although the population, especially young people have put aside their own identity to become part of a cultural alienation. Reason, the analysis of the alienation of cultural stereotypes from the city of Quito in FM radio programs in Latacunga is believed convenient….